Gaya Bahasa dalam Lirik Lagu “Epic Rap Battles of Presidency 2024” - Dahlena, Srik; Febria, Rhani (Jurnal Bahasa dan Sastra, 2024)
Hip hop music continues to evolve utilizing innovative and often rebellious language. More than just background music, hip hop song lyrics act as verbal manifestos, social commentary and poetic expression. This paper explores the intricate relationship between language style and hip hop song lyrics.  The method used in this research is a qualitative method. The data source in this research is the lyrics in the song entitled "Epic Rap Battles of Presidency 2024" sung by Andovi, Jovian de Lopez and Kristo Imanuel in the context of the 2024 Indonesian Presidential Election contestation. The data collection techniques are free listening and recording. The data analysis technique used is content analysis with a stylistic approach that focuses on the figurative language aspect. The results of the analysis show that the song lyrics of "Epic Rap Battles of Presidency 2024" utilize a number of figurative language including comparison consisting of hyperbole, personification, and metaphor; affirmation consisting of pleonasm, repetition, elepsis, and rhetoric, and satire consisting of sarcasm, irony, and cynicism. The use of figurative in song lyrics aims to create a beautiful impression and at the same time emphasize a number of messages that are meaningful to the intended parties, namely the presidential and vice presidential candidates in the 2024 Indonesian Presidential Election.